Ginsenoside-Rg1 mediates a hypoxia-independent upregulation of hypoxia-inducible factor-1α to promote angiogenesis - Leung, Kar-Wah (Springer Netherlands, 2011)
Hypoxia-inducible factor (HIF-1) is the key transcription regulator for multiple angiogenic factors and is an appealing target. Ginsenoside-Rg1, a nontoxic saponin isolated from the rhizome of Panax ginseng, exhibits potent proangiogenic activity and has the potential to be developed as a new angiotherapeutic agent. However, the mechanisms by which Rg1 promotes angiogenesis are not fully understood. Here, we show that Rg1 is an effective stimulator of HIF-1α under normal cellular oxygen conditions in human umbilical vein endothelial cells. HIF-1α steady-state mRNA was not affected by Rg1. Rather, HIF-1α protein synthesis was stimulated by Rg1. This effect was associated with constitutive activation of phosphatidylinositol 3-kinase (PI3K)/Akt and its effector p70 S6 kinase (p70(S6K)), but not extracellular-signal regulated kinase 1/2. We further revealed that HIF-1α induction triggered the expression of target genes, including vascular endothelial growth factor (VEGF). The use of small molecule inhibitors LY294002 or rapamycin to inhibit PI3K/Akt and p70(S6K) activities, respectively, resulted in diminished HIF-1α activation and subsequent VEGF expression. RNA interference-mediated knockdown of HIF-1α suppressed Rg1-induced VEGF synthesis and angiogenic tube formation, confirming that the effect was HIF-1α specific. Similarly, the angiogenic phenotype could be reversed by inhibition of PI3K/Akt and p70(S6K). These results define a hypoxia-independent activation of HIF-1α, uncovering a novel mechanism for Rg1 that could play a major role in angiogenesis and vascular remodeling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10456-011-9235-z) contains supplementary material, which is available to authorized users.